Chapter Subsidiarity to the Rescue for the European Courts? Resolving Tensions Between the Margin of Appreciation and Human Rights Protection - Føllesdal, Andreas (De Gruyter, 2016)
Contemporary esearch on federalism is rarely concerned with its philosophical foundations. However, arguments on why and how best to organise a plurality of states in a multilevel political order have first been discussed by philosophers and inspire contemporary reasoning on international relations not only in political philosophy. This book offers a unique overview from both a historical and a systematic perspective.